Pay Gaps and Mobility for Lower and Upper Tier Informal Sector Employees: an investigation of the Turkish labor market - Anil Duman (Global Labor Organization (GLO), 2020)
Many empirical studies found wage gaps between formal and informal sector workers even after controlling for a number of individual and firm level characteristics. While there is limited amount of research considering the same question in the Turkish labor market, wage gap between formal and informal employees generally do not take unobserved characteristics into account. In our paper, we carry this analysis for Turkey and estimate the wage gap between formal and informal sector workers utilizing panel data from Survey of Income and Living Conditions (SILC) for the period of 2014 and 2017. Mincer wage equations across quantiles are estimated considering observable and unobservable characteristics with a fixed effect model, and for sensitivity tests we regard the possibility of nonlinearity in covariate effects and estimate a variant of matching models. Our results show that informal wage penalty is persistent even after unobserved heterogeneity is taken into account, however, the penalty is not statistically significant at the upper end of the wage distribution. Moreover, we show that there are important differences between informal workers who have permanent contracts versus informal workers that have relatively more irregular work arrangements. Not only the latter is subject to earnings reductions, but they also have slightly lower probability of moving out of informal employment. We also demonstrate that the mobility of lower and upper tier informal workers is affected by different variables.
Keywords: J31; C31; O17; 330; wage gap; quantile regression; informal sector; panel data; Turkey